Implementasi Manajemen Sumber Daya Manusia Pada Event Organizer Future Work House di Provinsi Jambi - Aditya Darmawan; Sumarni Sumarni; Fitri Chairunnisa (Universitas 45 Surabaya, 2024)
The growth of the event organizer industry has grown rapidly in recent years. Future Work House is a business that offers services to organize and plan an event of both small and large scale. In practice, there are some unoptimal management functions such as employee recruitment, employee training and development, and human resource maintenance. This research aims to find out the implementation of human resources management that focuses on the recruitment, development and maintenance of employees at the event organizer Future Work House located in Jambi Province. The research carried out is a qualitative research conducted directly in the field through observations, interviews, and documentation. Furthermore, on the employee development of the company strives to continue to strive to develop employees with training but still not optimal. Because of the lack of specific training to develop new and old employees. So is the maintenance carried out by the company. The company strives to satisfy and make convenience to employees in order to increase employee loyalty. But there is still a shortage of methods used so that employees can feel good maintenance in the company.